Pengembangan Sistem Informasi Perpustakaan Dengan Pemanfaatan Fasilitas SMS Gateway - Machudor Yusman; Anie Rose Irawati; Rika Santika (Jurnal Komputasi, 2015)
Library information system is a system required by a library for managing the data and transactions in the library. Interactive information system is important for improving the quality of service in a library. An interactive system can produce useful information for users of the library. The dissemination of information that is more efficient can be done via the internet and mobile phones. This research, developed a library information system which is able to interact with members and visitors of the library and allowing members get information about books more quickly. Implementation of SMS Gateway with autoreply facility allows members to obtain books information anytime and anywhere. The system aim to simplify the process of updating information about new books to members of the library, add reading interest and increase the number of library visitors. System implementation used MySQL for database, GAMMU for SMS Gateway and PHP.Â Keywords: Gateway, Information, Interactive, Library, SMS, and System.